STRATEGI KEPALA SEKOLAH DALAM PEMBERDAYAAN KINERJA GURU PADA SMA NEGERI DI TRUMON RAYA - Dahniar Dahniar; Yusrizal Yusrizal; Nasir Usman (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2020)
The head master is top manager as the strategies roles in empowering the teacher performances. The purpose of this research is to know: arranging programs, the implementing programs, evaluation and obstruction challenging of the head master in empowering the teacher performances at SMA Negeri Trumon Raya. This research using qualitative research method descriptive. The techniques using to collected data those are: interview, observation, and documentation study. The subject of this research are head master and teachers. The results of this research show those are: menunjukkan (1) the arranging program conducted by the head master in empowering the teacher performances to analysis initial needed, from the result of analysis that defined what will discussed to developing the teacher performances. (2) The implementing strategy program in empowering the teacher performances in holding the MGMP training activities. For instances workshop, assigning each teachers to conduct the lesson plan, harnessing the peer teachers in circumstances, and the teacher facilities needed. The strategy conducting by the head master is the ways to organizing the function as the tool in communication, share knowledge, thinking, and experiences in increasing the teacher performances. (3) The evaluation program conducting with the way is academics supervision with the visiting classroom techniques. And (4) the obstruction faced by the head master those are lack of indiscipline’s of teacher, tendency of teacher in copy paste the lesson plan, and less of competence of teachers in mastering the learning technology, lack of facilities in supporting the learning process. Abstrak Kepala sekolah sebagai top manager memiliki peran yang sangat strategis dalam memberdayakan kinerja guru. Tujuan penelitian ini untuk mengetahui: penyusunan program, strategi pelaksanaan program, evaluasi dan hambatan yang dihadapi kepala sekolah dalam perberdayan kinerja guru pada SMA Negeri di Trumon Raya. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Teknik pengumpulan data yang digunakan adalah: wawancara, observasi dan studi dokumentasi. Subjek penelitian adalah kepala sekolah dan guru. Hasil penelitian menunjukkan bahwa: (1) penyusunan program yang dilakukan kepala sekolah dalam pemberdayaan kinerja guru dengan menganalisis kebutuhan awal, dari hasil analisis tersebut baru ditentukan apa yang harus dilakukan untuk mengembangkan kinerja guru; (2) Strategi pelaksanaan program pemberdayaan kinerja guru dengan menyelenggarakan kegiatan pelatihan MGMP, pelatihan berupa workshop, menugaskan setiap guru mata pelajaran untuk membuat perangkat pembelajaran, memanfaatkan tutor sebaya sesama guru dilingkungan sekolah, dan memfasilitasi guru terhadap keperluannya. Strategi yang dilaksanakan kepala sekolah merupakan wadah asosiasi yang berfungsi sebagai sarana untuk saling berkomunikasi, bertukar ilmu, fikiran dan pengalaman dalam rangka meningkatkan kinerja guru; (3) evaluasi program dilakukan dengan cara melakukan supervisi akademik dengan teknik kunjungan kelas, dan (4) kendala yang dihadapi adalah kurangnya kedisiplinan guru, kecendering guru melakukan copy paste dalam mencari bahan ajar, keterbatasan kemampuan guru dalam menguasai teknologi pembelajaran, kurangnya fasilitas penunjang proses pembelajaran.